Familial Occurrence of Atrioventricular Nodal Reentrant Tachycardia. (February 2017) - Michowitz, Yoav; Anis-Heusler, Adi; Reinstein, Eyal; Tovia-Brodie, Oholi; Glick, Aharon; Belhassen, Bernard
Abstract : Background—: Atrioventricular nodal reentrant tachycardia (AVNRT) is considered a sporadic disease occurring in ≈22.5 cases per 10 000 in the general population. We define the prevalence and characteristics of familial AVNRT among patients who underwent radiofrequency ablation. Methods and Results—: Ablation reports of all patients with familial AVNRT (at least 2 first-degree family members) who underwent radiofrequency ablation in our institution and in another hospital were reviewed. There were 1587 patients from our institution, of whom 20 had ≥1 first-degree relatives with AVNRT. This indicates a familial AVNRT prevalence of 127 cases per 10 000 (95% confidence interval, 82–196/10 000). First-degree relatives of patients with AVNRT presented a hazard ratio of at least 3.6 for exhibiting AVNRT compared with the general population. After inclusion of 4 families with familial AVNRT who underwent ablation at another hospital our population study comprised a total of 24 families (50 patients) with AVNRT. Patients at ablation were younger in the familial AVNRT group when compared with the sporadic AVNRT group (44.2±19 versus 54.8±18 years old, P =0.0001). The male/female ratio was similar, with female predominance. The supraventricular tachycardia mechanism was typical slow/fast reentry in most cases in both groups. The most common familial relationship in our 24 families included a parent and a child in 67% of cases and less often 2 siblings (29%). Conclusions—: Familial AVNRT prevalence is higher than previously believed suggesting that this arrhythmia may have a genetic component. Autosomal dominance with incomplete penetrance is the most likely mode of inheritance.